2021
DOI: 10.3389/fpls.2020.593984
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Euonymus Chloroplast Genomes: Genetic Structure, Screening for Loci With Suitable Polymorphism, Positive Selection Genes, and Phylogenetic Relationships Within Celastrineae

Abstract: In this study, we assembled and annotated the chloroplast (cp) genome of the Euonymus species Euonymus fortunei, Euonymus phellomanus, and Euonymus maackii, and performed a series of analyses to investigate gene structure, GC content, sequence alignment, and nucleic acid diversity, with the objectives of identifying positive selection genes and understanding evolutionary relationships. The results indicated that the Euonymus cp genome was 156,860–157,611bp in length and exhibited a typical circular tetrad stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 105 publications
12
33
1
Order By: Relevance
“…In the present study, except in morphological confusing species S. albescens , S. dunnii , and S. velutina , the rps12 gene lost an intron in this genus which was specific to Desmodieae ( Jin et al, 2019 ). We also identified the addition of an intron in ndhA , atpF , rps16 , and rpoC1 , a finding which differs from those of previous studies ( Li et al, 2021 ; Oyebanji et al, 2020 ; Zhao et al, 2020 ; Guo et al, 2021 ). Compared to the two species ( S. macrocarpa and S. toromiro ) distributed in Chile, the ycf3 gene was increased by one to two introns and the gene rrn23 lost introns within each of the taxa distributed in China.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In the present study, except in morphological confusing species S. albescens , S. dunnii , and S. velutina , the rps12 gene lost an intron in this genus which was specific to Desmodieae ( Jin et al, 2019 ). We also identified the addition of an intron in ndhA , atpF , rps16 , and rpoC1 , a finding which differs from those of previous studies ( Li et al, 2021 ; Oyebanji et al, 2020 ; Zhao et al, 2020 ; Guo et al, 2021 ). Compared to the two species ( S. macrocarpa and S. toromiro ) distributed in Chile, the ycf3 gene was increased by one to two introns and the gene rrn23 lost introns within each of the taxa distributed in China.…”
Section: Discussioncontrasting
confidence: 98%
“…AT/AT repeats, AAT/AAT repeats, and AAAT/AAAT repeats were prevalent in all species ( Figure 3A ). This phenomenon may occur because the A/T variation occurs more easily than the G/C mutation ( Li et al, 2021 ). Similar cases has been reported in previous study in which SSRs generally consist of polyA or polyT repeats, and rarely contain G or C repeats ( Zha et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated these protein-coding genes are under strong structural and functional constraints. The absence of positive selection in most protein-coding genes of chloroplast genome was also found in Euonymus ( Li et al, 2021 ) and Quercus ( Yin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 71%
“…Chloroplasts are semi-autonomous replication organelles, originating in endosymbiosis between cyanobacteria and non-photosynthetic host, and play crucial roles in photosynthesis and physiology of plants ( Gao et al, 2019a ; Huo et al, 2019 ; Li et al, 2021 ). The chloroplast genome is mostly a typical quadripartite circular DNA genome comprising a small single-copy (SSC), a large single-copy (LSC), and two inverted repeats (IRs) ( Hu et al, 2016 ; Chang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, 110 SSRs were identified from the cp genomes of two Zingiber species, and the most abundant repeat type was AT/TA, followed by A/T mononucleotide repeat. Previous studies found that cp genome SSRs always consists of short poly-A or poly-T repeats, and most plants rarely contain tandem G or C repeats ( Li et al, 2021 ). At present, SSR markers have been widely used in the fields of species identification, genetic diversity, population structure evaluation, comparative genomics, and marker-assisted selection breeding ( Zhang et al, 2019 ; Liang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%